(untitled) (Colombia Medica, 1987)
This paper reports a case of Norwegian scabies associated with oral moniliasis and lymphatic and pulmonary tuberculosis in a patient with adult T-cell lymphoma/leukemia. Clinical and histopathological criteria were used to establish diagnoses.